Periodontal Status, Behavioral Risk Factors, and Community-Based Surveillance of Type 2 Diabetes Mellitus - ijiemrMuhammad Azhar Khan, Touseef Ansar, Shabir Ahmad, Muhammad Akram Cheema, Misbah Ul Hasan Ghani, Muhammad Sami Iqbal, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The bidirectional relationship between periodontal disease and type 2 diabetes mellitus (T2DM)has been increasingly recognized as a critical determinant of systemic and oral health. This cross sectional community